Facilitating the implementation of LNG as an alternative fuel technology in landlocked Europe: A study from Austria. (March 2016) - Pfoser, Sarah; Aschauer, Gerald; Simmer, Laura; Schauer, Oliver
Abstract: Liquefied Natural Gas, LNG, is known to be an innovative alternative fuel technology. However, there are severe barriers which impede the application of LNG in the landlocked areas of Europe. Above all, the necessary infrastructure which could stimulate the spacious application of LNG is still lacking there. The objective of the present work is therefore to build a basement for launching LNG in this region. This will be carried out in two stages: First by deliberately examining the potential demand for LNG to see if the construction of LNG infrastructure is viable in this region and second by identifying the stakeholders which have to be taken into account to successfully accomplish this process. Therefore, a demand analysis has been carried out by interviewing 15 potential Austrian pioneer users with capacious vehicle fleets. Their requirements towards LNG application have been categorized and prioritized using Maslow's hierarchy of needs. Finally, a stakeholder matrix evaluates crucial stakeholders and gives an indication of how to deal with them appropriately. The results reveal that interest for LNG exists and the potential for introducing LNG in landlocked Europe is given.